计算[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/08 06:22:15
计算[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)计算[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)计算[(2a^2bc)^3-6a^3b-(-
计算[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)
计算[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)
计算[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)
[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)
=(8a^6b^3c^3-6a^3b-16a^2b^4)/(2a^2b)
=4a^4b^2c^3-3a-8b^3
约简分式:(a-b)^2 /(a-b)^3 计算:(-3a/bc^2)^2 (3a/a-b)^2
计算[(2a^2bc)^3-6a^3b-(-4ab^2)^2]/(2a^2b)
(-a²b^-3c^-1)²·(-1/2a^-2bc^-2)^-1计算
计算:(a+b)(2a-3b)
计算(a^4b^3c)+(2a^2b^3)*(-3分之2a^3bc^2)
计算(8a^4b^3c)÷(2a^2b^3)×(-2/3a^3bc^2)
已知a^+b^+c^-ab-bc-ca=0,计算(a^+b^+c^+2ab+2bc+2ca)÷3(a^+b^+c^)的值
计算(a-b)(b-a)^3+[(a-b)^2]^2
计算a/a+2b-b/3a-b
计算(5a-3b)^2+(a+b)(a-b)
已知a-b=3,b+c=5,计算代数式ac-bc+a^2-ab的值.
计算:(4a-b)(3a+2b)-6a(3a+b)
计算a^-2bc^-1÷(-b^2c)^3明天之前尽快啊
计算3(a+b)-2(a-b)-a=
已知a+bc=14,b-2bc=-6,则3a+4b-5bc=()
计算:(4a-b)^2-[8a*(a-b)-(3a-b)*(3a+b)]
计算a+[a+b]+[a+2b]+[a+3b]+...+[a+99b]
计算:a+(a+b)+(a+2b)+(a+3b)+……+(a+99b)